International criminal justice at the interface: the relationship between international criminal courts and national legal orders - Bekou, Olympia (2005)
International criminal courts do not operate to the exclusion of national legal orders, but co-exist with them. The present thesis provides an in-depth analysis of the above relationship. By examining the concepts of primacy and complementarity on the basis of which the ad hoc international criminal Tribunals and the permanent International Criminal Court seize jurisdiction, the foundations of the interface are explored. As effectiveness is a key concept to international criminal justice, the relationship between international criminal courts and national legal systems is tested, by examining the co-operation regimes envisaged in the Statutes of both the Tribunals and the ICC, as well as the problems that arise in practice. Moreover, the way the UN Security Council affects State interplay with international criminal justice institutions is crucial for a holistic understanding of the limitations of the interaction. The final part of the thesis focuses on national incorporation efforts and provides a detailed analysis of implementing legislation of a number of key States with a view to discerning some common approaches and highlighting problem areas. The present thesis argues that despite the different constitutional bases of the Tribunals and the ICC, similar questions of interface with national courts arise and the challenges presented could be better tackled by aiming for a "functional or workable interaction". Overall, the originality of this thesis lies in its analytical approach. By scrutinising a number of crucial aspects of the relationship between international criminal courts and national legal orders an overview of the research question posed is achieved. Moreover, the examination of the legal principles and their practical application is complemented by a comprehensive discussion of national implementing legislation which has not previously been attempted in a similar manner.